Thyroid Function after Coronary Angiography and Angioplasty - Sviridenko, N Y; Platonova, N M; Egorov, A V; Samko, A N; Naumov, V G; Ezhov, M V; Buziashvili, Y I; Tugeeva, E F (Klinicheskai͡a︡ i ėksperimentalʹnai͡a︡ tireoidologii͡a, 2007)
The issue of this study was the investigation of the frequency of the thyroid functional disorders after administration of the iodine-containing contrast media in patients located in iodine deficient region. 146 patients were examined, before and after the coronary angiography. Initially, the high frequency of the thyroid pathology was discovered (39%). The thyroid functional state and the urinary iodine excretion were estimated before and 1, 3, 6 and 12 months after the study. During 1 month after the coronary angiography several cases of thyrotoxicosis and hypothyroidism relapse were fixed, and also the deterioration of the course of the already present thyroid functional disorders was registered. The patients with the initial pathology and the thyroid functional disorders should be included into the risk group by the development of the iodine induced thyroid dysfunction.